Undergraduate business student perceptions of teaching presence in online classes - Makani, Betty (Kansas State University, 2015)
The purpose of this study was to examine undergraduate business student perceptions of teaching presence in order to scale up online learning to improve access to quality education. This study also responded to Senate Bill 520, calling for the improved online course quality. The data were obtained from 437 undergraduate business students (response rate 79.17%). A non-experimental, cross-sectional survey design was used, incorporating the Teaching Presence Scale and Lukow’s Attitudes Towards the Use of Technology Survey. Teaching Presence was the theoretical framework. Data analysis regarding the participants’ personal characteristics indicated that their perceptions of teaching presence were not influenced by age. A statistically significant difference was found in the participants’ perception of teaching presence by gender (p<.05), as well as instructional design, and course organization. Data analysis regarding participants’ contextual characteristics indicated that perceptions of teaching presence were not influenced by course duration. However, a statistically significant difference was found in the participants’ perception of teaching presence based on class level, p<.05. Significant differences were found in communication, assessment and feedback. Data analysis of technographic characteristics found no statistically significant influence on participants' perception of teaching presence. Recommendations for the research setting were in the areas of learning environment engagement, online teaching pedagogy, online course materials development, communication and feedback, faculty development and student technology resource and support. Future research on perceptions of teaching presence from the instructor’s perspective, student characteristics in terms of race and ethnicity, impact of audio and video feedback, and expansion of the student population to other disciplines were recommended.
Keywords: Online learning; Undergraduate students; Business; Student PerceptionsTeaching presence; Business (0310); Curriculum Development (0727); Education, Technology (0710)